Mendongeng Bersama Anak Sebagai Upaya Pencegahan Covid-19 - Sulastri, Ni Made; Maharani, Jessica Festy; Sarilah, Sarilah (Jurnal Pengabdian UNDIKMA, 2020)
Community service activities aim to increase children’s knowledge about co-19 in a fun way so that it is easily understood by children, this is done on the grounds of children’s activities while at home, studying at home so it is necessary to do interesting activities so that the growth and development of children continues to develop well. Various choices of activities can be done in accordance with the principles of children’s learning, namely learning through play, one of the fun activities that can be done by children is through storytelling activities. Storytelling activities can use pictorial story book media, storytelling with hand puppets or finger puppets, and can also use digital-based media in conveying a fairy tale to children, online media is felt to be the most appropriate way to facilitate storytelling activities in children during the pandemic covid 19 this. Storytelling activities are aimed at making children have play activities while learning about Covid-19, children are expected to be able to easily understand how to prevent covid-19, healthy ways of living, so that children can understand and can enjoy learning activities while at home with fun.